Palmoplantar plaque psoriasis responsive to upadacitinib: A report of two cases - Bohmyi Choi; Heidi Oi-Yee Li; Steven J Glassman (SAGE Open Medical Case Reports)
Palmoplantar plaque psoriasis is more resistant to therapy compared to other phenotypes of psoriasis. To our knowledge, there are no reports of the efficacy of Janus kinase (JAK) inhibitors for palmoplantar plaque psoriasis. Two adult females presented with more than 6-year histories of severe palmoplantar plaque psoriasis. The first patient had failed topical therapies, phototherapy, acitretin, and secukinumab. The second patient had failed topical therapies and systemic agents including alitretinoin, cyclosporine, apremilast, ustekinumab, ixekizumab, and risankizumab. Both cases were switched to upadacitinib 15 mg daily, with a complete response by 3 months of therapy and no adverse events. The first patient had slightly elevated fasting triglyceride and the second patient had elevated ALT, both of which are being monitored. This case series highlights the efficacy of upadacitinib in two patients with refractory palmoplantar plaque psoriasis. JAK1 inhibitors may be considered as third-line therapeutic options in patients with refractory palmoplantar plaque psoriasis and no contraindications to JAK inhibitors.